2022
DOI: 10.7759/cureus.24207
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into the Distribution of Allele Frequency of ABO and Rh (D) Blood Grouping System Among Blood Donors in a Tertiary Care Hospital in Chengalpattu District of South India

Abstract: Introduction The distribution of ABO and Rh (D) blood groups and their allele frequencies vary from one population to another worldwide. The objective of the study is to estimate the distribution of ABO & Rh (D) blood groups among all the blood donors in a tertiary care hospital in Chengalpattu district of Tamilnadu in South India and to determine their allele frequencies. Methods This was a retrospective observational study carried out in the blood bank of Karpaga Vinayaga Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…According to our findings, the Rh-positive blood group accounted for 97.7% of all cases. Rh-negative was only 2.2% in contrast to other studies which showed a range between 5-17%, except in Britain and United States of America, where data showed 15-17% Rh-D negative [15]. However, the findings are consistent with previous research from Tanzania and India, where the incidence of Rh-D negative blood group was 2.3% and 2-6%, respectively [5].…”
Section: Resultssupporting
confidence: 86%
“…According to our findings, the Rh-positive blood group accounted for 97.7% of all cases. Rh-negative was only 2.2% in contrast to other studies which showed a range between 5-17%, except in Britain and United States of America, where data showed 15-17% Rh-D negative [15]. However, the findings are consistent with previous research from Tanzania and India, where the incidence of Rh-D negative blood group was 2.3% and 2-6%, respectively [5].…”
Section: Resultssupporting
confidence: 86%
“…For instance, studies from India, Ethiopia, Libya, Turkey, and Namibia demonstrate varied distribution patterns, often influenced by the complex interplay of ethnicity and regional characteristics. In South India, the most common blood group was O positive, a stark contrast to the prevalence of group B in our study (11). Similarly, the Ethiopian population showed a predominance of blood group O, aligning more closely with the findings of our study (2).…”
Section: Discussionsupporting
confidence: 89%
“…In Western Europe, the distribution is 46% for type O, 42% for type A, 9% for type B, and 3% for type AB. A study in Ogbomoso, Oyo State, Nigeria, involving 7,653 participants, revealed that 50% had blood type O, 22.9% type A, 21.3% type B, and 5.9% type AB (2,3,5,11). These variations underscore the influence of genetic and environmental factors on blood type distribution and necessitate localized studies to understand these dynamics better (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…In our study majority were males (99.4%). It is similar to several other studies conducted in different parts of India [3,8]. Some of the reasons behind less female donors include anemia, low weight, lack of motivation, and fear of blood donation.…”
Section: Discussionsupporting
confidence: 88%
“…We compared ABO & Rh (D) distribution across different states of India [3,[10][11][12][13][14][15][16][17][18][19][20] ( The distribution of ABO blood group varies across neighbouring [21][22][23] & other countries [24][25][26][27][28] of the world as seen in Table 5. In India O & B phenotypes are common; whereas in America [27] & Europe [28] O & A phenotypes are common.…”
Section: Discussionmentioning
confidence: 99%